Dynamic thermal analysis of startup process for minichannel evaporator. (September 2022) - Li, Guanru; Zheng, Yi; Tao, Jianyun; Liu, Xiangdong; Zhang, Chengbin
Highlights: Start-up regimes of minichannel evaporator are formulated by transfer function. Evaluation criteria in control theory are proposed to describe start-up behaviors. Startup performances of minichannel evaporator are quantitatively investigated. Working fluid with small subcooling degree is beneficial for evaporator start-up. Evaporator temperature overshoot can be alleviated via increasing heat load. Abstract: The start-up performance of minichannel evaporator in a mechanically pumped two-phase loop (MPTL) is investigated in terms of the dynamic temperature response. A preliminary start-up regime diagram is identified, where temperature response of start-up process can be recognized as three modes, including the gradual start-up, once-rise overshoot start-up and twice-rise overshoot start-up. Theoretical analysis and model identification are conducted via Laplace-transformation and representative evaluation criterion is proposed to realize the quantitative characterization of specific start-up mode. Time constant and settling time act as the indicators to evaluate temperature response rate, while overshoot is utilized to assess the two-phase flow instability. The results indicate that: for gradual start-up mode, the time to reach quasi-steady state is smaller as heat transfer performance improves via increasing heat load, while temperature response rate is relatively insensitive to flow rate; for once-rise overshoot start-up mode, the two-phase flow instability can be alleviated via increasing the heat load, while the increment of flow rate could intensify the instability; for twice-rise overshoot start-up mode, the temperature overshoot is insensitive to heat load variation. Moreover, preheating the working fluid at evaporator inlet is beneficial to mitigate the instability, indicating that preheater/regenerator can optimize the robustness/stability of start-up.